An investigation on machinability assessment of Al-6XN and AISI 316 alloys: an assessment study of machining. Issue 2 (4th March 2019) - Alabdullah, Mohanad; Polishetty, Ashwin; Nomani, Junior; Littlefair, Guy
Abstract: This work presents machinability assessment of AL-6XN super austenitic stainless steel alloy. Cutting forces, surface roughness, work hardening tendency and tool wear were analyzed. The assessment was conducted based on a comparison between the AL-6XN alloy and the well-known alloy in the machining field AISI 316. Finite element analysis (FEA) study was also conducted and used in this assessment. Experimental results showed maximum increase of 70% and 57% in the feed and normal forces of the AL-6XN alloy, respectively. Maximum increase in the work hardening tendency of 59% was recorded for the AL-6XN alloy while only 29% was recorded for the 316 alloy. The roughness analysis recorded an increase of 186% for the AL-6XN alloy compared to the 316 alloy. Tool wear analysis revealed the build-up edge formation, severe chipping, flank and crater wear (CW) during cutting AL-6XN alloy whereas small chipping, flank and CW were noticed during cutting 316 alloy. FEA study showed when the AL-6XN alloy machined using 65 and 94 m/min cutting speeds, the increases (compared to the 316 alloy) were: 12% and 8% in plastic strain; 20% and 20% in stresses; 48% and 100% in residual tensile stresses; 22% and 92% in residual compressive stresses, respectively.